Análise comparativa citogenética e molecular em acessos de Stylosanthes e de déficit hídrico em acessos de Macroptilium - Lira, Irlane Cristine de Souza Andrade (2022)
This work aimed to characterize accessions of forage legumes of the genera (Stylosanthes and Macroptilium) with a view to identifying materials with potential for use in breeding programs aimed at animal feed. Accessions of the genus Stylosanthes were evaluated through cytogenetic and molecular characterization. Regarding the genus Macroptilium, a study was carried out on the effect of water deficit on the vegetative development of this genus. The data obtained were subjected to analysis of variance, test of means and regression analysis. As a result of the cytogenetic characterization, 13 Stylosanthes accessions of the species S. scabra and S. seabrana were cytogenetically evaluated, identifying the number, chromosomal morphology and heterochromatin distribution pattern in order to study the karyological variability in support of the characterization of the species. Accessions with 2n=40 (S. scabra) and 2n=20 (S. seabrana) chromosomes, semi-reticulated interphase nucleus, symmetrical karyotype with chromosomal morphology ranging from metacentric to submetacentric and mean chromosome size of around 2.5 µm were observed. with differences in mean chromosome length and total genome length. The analysis with double CMA/DAPI staining allowed the visualization of two CMA+ blocks in the accessions of both species located in the subterminal region of the short arm of the smallest chromosome pair, it was also possible to visualize DAPI+/CMA- bands in two of the ten accessions of S scabra (accessions CPAC 1261 and CPAC 5205). In the molecular characterization, 104 polymorphic bands and only four monomorphic bands were produced. The similarity coefficients calculated from the Dice method (Sorenso - Nei and Li) ranged from a minimum of 0.06349 to a maximum of 0.70588 in distance. From the dendrogram obtained, it was possible to separate the accessions into five groups, where Group 1 was formed by 14 components, Group 2 formed by only 1 accession; Group 3 formed by 3 accessions, Group 4 formed by the cultivar BRS Campo Grande; and the last Group 5, formed only by the cultivar BRS Bela. With regard to Macroptilium, when subjected to water deficit, it was observed that the accessions that were more tolerant to the most severe water stress level (soil moisture of 25% of CC), even many times higher than the control CTM-A27, were the CTM-A15, of the species M. atropurpureum, followed by the accessions CTM-A3 and CTM-A54. Among the M. lathyroides accessions, the most tolerant were the accessions CTM-L27 and CTM-L7, these being the most recommended accessions for use in future breeding programs for the species for drought conditions. The results of this study allow inferring that there is great variability within the germplasm of the two genera studied, which enables its use in selection and genetic improvement programs.